LITERATURE REVIEW: ANALYSIS OF LOGISTICS INVENTORY MANAGEMENT IN PHARMACY SERVICES - Maria Anita Yusiana (Pedagogic Research-Applied Literacy Journal, 2024)
This study aims to analyze logistics management and supplies in services in pharmacy installations, presenting an overview of logistics inventory management in pharmacy installations and various management of processing supplies in pharmacy. The writing method used in content analysis is by searching 10 journals from correct literature reviews in various journal sources in Indonesia. The results of the literature review show that the quality of services provided by hospitals greatly influences the image of the hospital and the satisfaction of patients who visit the hospital. Factors that influence the role of hospitals in managing drugs in hospitals and managing drugs in pharmacies are very necessary to prevent drug shortages and excess drugs caused by an increase in the number of patients. In conclusion, in these 10 journals, analyzing inventory management and its description is carried out from good input and processes, then in overcoming control of drug supplies, this can achieve the desired targets in accordance with the strategies and programs set by the government.